2013
DOI: 10.1530/eje-12-0327
|View full text |Cite
|
Sign up to set email alerts
|

MEN1 intragenic deletions may represent the most prevalent somatic event in sporadic primary hyperparathyroidism

Abstract: Objective: Primary hyperparathyroidism (pHPT) is characterised by an inappropriate over production of parathyroid hormone and it is the most frequent pathological condition of the parathyroid glands. A minority of the cases belong to familial forms, but most of them are sporadic. The genetic alterations underlying the sporadic forms of pHPT remain poorly understood. The main goal of our study is to perform the molecular characterisation of a series of sporadic pHPT cases. Design and methods: We have studied ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Expression studies regarding menin and associations to underlying MEN1 mutational status in parathyroid tumors have been promising, as menin immunohistochemistry seem to exhibit high sensitivity to detect underlying MEN1 mutations and/or gene deletions [132,133]. Even so, the interpretation of menin immunohistochemistry is not straightforward, and the lack of comprehensive studies on the subject makes menin immunohistochemistry inappropriate for clinical routine screening purposes.…”
Section: Men1-related Phpt: Could the Pathologist Be Of Any Help?mentioning
confidence: 99%
“…Expression studies regarding menin and associations to underlying MEN1 mutational status in parathyroid tumors have been promising, as menin immunohistochemistry seem to exhibit high sensitivity to detect underlying MEN1 mutations and/or gene deletions [132,133]. Even so, the interpretation of menin immunohistochemistry is not straightforward, and the lack of comprehensive studies on the subject makes menin immunohistochemistry inappropriate for clinical routine screening purposes.…”
Section: Men1-related Phpt: Could the Pathologist Be Of Any Help?mentioning
confidence: 99%
“…(Yokoyama et al, 2005) A recent study reported MEN1 intragenic deletions in 13/24 parathyroid adenomas using FFPE material, but this alteration remains to be reproduced. (Alvelos et al, 2013) Multiple endocrine neoplasia type 2 (MEN 2)…”
Section: Epidemiologymentioning
confidence: 99%
“…4B). The importance of chromosome 11 in parathyroid pathogenesis is well established, because the MEN1 gene maps at 11q13.1, ( 30 ) and MEN1 ‐inactivating mutations through LOH at 11q are the most frequent finding in sporadic adenomas. ( 28 ) In keeping with this, PAds with chr11 normal haplotype showed higher MEN1 mRNA expression than adenomas with chr11‐LOH ( p = .03; Fig.…”
Section: Resultsmentioning
confidence: 99%